The Philosophical Foundations of Islamic Political Economy (American Journal of Islam and Society, 1996)
Then we put thee on the right way, So follow thou that; And follownot the desires of those who know not. (Qur'an 45: 18)IntroductionWestern perceptions of Islam have always been colored by their fearof Islamic expansion and the historical rationality of the Crusades. Thecurrent preoccupation with the "clash of civilizations" debate and theextraordinary focus on "Islamic fundamentalism" have greatly politicizedthe discourse on Islam while preventing a fuller understanding of Islam.The tendency among Muslim scholars to allow the West to set the agendaof what should be studied in and about Islam has led to the delay of ijtihadin more important areas, such as Islamic political economy. In the age ofmodernization, thinkers in the West have rejected Islam as backward lookingand as an impediment to economic development. A fair interpretationof Islam, however, includes a complete understanding of the need fordevelopment and social welfare. The political economy of Islam, as thispaper will present, is a completely humanistic and internally consistentdevelopment and welfare-oriented paradigm.In the twentieth century, Islam has survived colonial domination,communist repression, and the rapid spread of liberalism. Today it has arapidly increasing membership of over one billion and is experiencing aresurgence from Malaysia to Sudan and Algeria and from Iran to thenewly independent republics of Central Asia. More and more nations withpredominantly Muslim populations are undergoing a burgeoning sense ofIslamic consciousness. To some, this is a cohesive global phenomenonwith potentially indelible consequences. They see it as a radical movementthat is antithetical to Western liberal values and a challenge to theirreligious zeal to universalize these values. Regardless of the political constructionsof Islam's revival, what is of the essence is that more and more ...